Environmental Challenges – Strategic Responses - Bartók, István (International Journal of Engineering and Management Sciences, 2017)
The paper serves the purpose of understanding better how businesses and enterprises may handle the changes happening in their environment using the tools of management. Radical changes are happening in the environment of businesses, primarily as a result of the massive and forceful appearance of new opportunities and constraints brought by the technological development. Some of the businesses participates actively in the creation of changes. For other businesses the main issue is the way they may handle the changes. How may businesses and enterprises adapt to the new environmental characteristic is the main issue under scrutiny in this paper.